Strategi Penguatan Kelembagaan Usaha Minuman Olahan Berbahan Baku Sirsak di Kabupaten Kediri - Novi Haryati; Arif Wahyu Setiawan; Excel Virgi Swastika (Agro Ekonomi, 2016)
Processing is one solution in handling perishable and durable agricultural products. This study aims to determine: (1) production-based region of soursop commodities in Kediri, (2) analysis of strengths, weaknesses, opportunities and threats in soursop-based small entreprise, and (3) strategy of institutional strengthening implemented within the business. Primary data was taken through interview and secondary data was derived from the Central Statistics Agency of Kediri from 2010 to 2015. Research location was determined by judgment sampling which is located in the small business of Wonojoyo Trisulo in Plosoklaten. Research shows that Beside Plosoklaten, LQ analysis described other 12 production-based area of soursop in Kediri, such as Gurah, Kandat, Tarokan, Wates, Kepung, Ngancar, Mojo, Ngasem, Pagu, Gampengrejo, Semen, and Ngadiluwih. Those area will contribute as opponent for Plosoklaten to produce good quality product of soursop. SWOT analysis shows that the business’s position is in quadrant IV (negative, negative) that indicates the condition of weak, because it has some weaknesses and threats from the outside environment more than the strength and opportunity. Damage Control considers as an appropriate strategy that can be done by conducting more market-oriented management. Human resources and technology are also needed to be improved in the future.